In the Beginning - Penny Frank; Tony Morris (UK USA Lion Publishing, 1985)
A retelling of Genesis, Chapter 1, in which God creates the world and everything in it.
col. ill. ; $1.95 (U.S.) Australia
"A Lion book"--P. [4] of cover.
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Creation -- Juvenile literature; Theology; Creation; Bible stories -- Old Testament